2021
DOI: 10.1021/acs.jced.0c00449
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[a]pyrene: Standard Thermodynamic Properties from Adiabatic and Combustion Calorimetry and Density Functional Theory

Abstract: The temperature dependence of heat capacity of polycyclic aromatic hydrocarbon, benzo[a]pyrene, was investigated in the temperature range T = 7.5−329.3 K using adiabatic calorimetry. Smoothed C p,m °(T) values between 0 and 329 K are presented along with values for the standard thermodynamic functions:pyrene has been determined using the isothermal combustion calorimeter with a stationary bomb. These new experimental results, together with literature data, are used to calculate the standard enthalpy of formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Of the 24 PAHs for which the experimental enthalpies of formation were recommended in the review by Roux et al, the accuracy of the experimental values was confirmed for only half of the compounds. Among more recent experimental measurements, the discrepancies from 6 to 34 kJ/mol were obtained for eight compounds. ,,,, Thus, this study shows that modern quantum chemical methods increase the accuracy of computations to a level that is comparable to, and in some cases exceeds, the accuracy of current thermochemical determinations, particularly for systems that are difficult to study experimentally.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Of the 24 PAHs for which the experimental enthalpies of formation were recommended in the review by Roux et al, the accuracy of the experimental values was confirmed for only half of the compounds. Among more recent experimental measurements, the discrepancies from 6 to 34 kJ/mol were obtained for eight compounds. ,,,, Thus, this study shows that modern quantum chemical methods increase the accuracy of computations to a level that is comparable to, and in some cases exceeds, the accuracy of current thermochemical determinations, particularly for systems that are difficult to study experimentally.…”
Section: Discussionmentioning
confidence: 63%
“…Comparison with Experimental Data. The recommended gas-phase enthalpies of formation of reference PAHs were taken from the critical review of Roux et al 3 with the exception of indene (2), indane (3), pyrene (13), and benzo[e]pyrene (24). The new experimental data for indene, 25 indane, 26 and pyrene 29 are very close to those recommended earlier, 3 but have smaller uncertainties, whereas the experimental data for benzo[e]pyrene (24) 23 have been obtained recently for the first time.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations